Pengaruh Sosio-Demografi Terhadap Sikap Pemilihan Mata Pelajaran Ekonomi - Wee, Hock Seng (1998)
The awareness of economic knowledge is essential in developing and maintaining our country economy. This siuation is necessary with the development and achievement in Science and Technology. The lack of economic knowledge will give negative impact in our effort to provide prosperity to our people and at the same time make our country economy much stronger. Therefore, economic knowledge should start at secondary school school level. This research attempt to analyse how socio-demography factors influence students attitude towards selecting the curriculum, principle of economic beginning from form 4. The study covers school in the districts of Tanah Merah and Machang, Kelantan. The main objectives of this research is to investigate the relationship between factors such as demography, parent support, parent-socio-economic, teachers influences, peers influence and academic achievements with student attitude towards the choice of principle of economic subject. This research were carried out on 253 form four students which took principle of economic subject at 10 school. The required data were collected through the use of questionnaires, comprising 58 questions. Statistical methods used in this research were Pearson’s Correlation, ANOVA, t-test, cross-tabulation Chi-Square and Multiple Regression Analysis (MRA). The result showed that the variables parents support, teachers influences and academic achievements are significant relationships between student attitude towards the choice of principle of economic subject. The study R2 obtained was reasonable good at 57.7 %.